2023
DOI: 10.1038/s41417-022-00582-y
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals changes in glioma-associated macrophage polarization and cellular states of malignant gliomas with high AQP4 expression

Abstract: Glioma is the most common primary central nervous system tumor in adults. Aquaporin-4, as a water channel protein encoded by AQP4 in the brain, is reported to alter its aggregation status to affect plasma membrane dynamics and provide the potential for metastasis of tumor cells and components of the tumor microenvironment. We performed single-cell RNA transcriptome sequencing of 53059 cells from 13 malignant glioma samples and spotted that the expression of AQP4 differed between samples. The same result was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The AQP4_Astro cluster may represent some common features between EPN and BG. Evidence has demonstrated that AQP4, which is usually highly expressed in brain tissues, promotes the tendency of tumor-associated macrophages to become M1 macrophages, thereby causing alterations in the cellular state of gliomas [ 37 , 38 ]. Increased expression of AQP4 leads to a reduced OS in malignant gliomas, resulting in a poor prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AQP4_Astro cluster may represent some common features between EPN and BG. Evidence has demonstrated that AQP4, which is usually highly expressed in brain tissues, promotes the tendency of tumor-associated macrophages to become M1 macrophages, thereby causing alterations in the cellular state of gliomas [ 37 , 38 ]. Increased expression of AQP4 leads to a reduced OS in malignant gliomas, resulting in a poor prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings begin to deconstruct complex TAM-GBM cell interactions and support ongoing therapeutic efforts aimed at repolarizing M2 macrophages towards M1-like polarization states, as well as offering novel therapeutic targets that could prevent the potent effects of M2 macrophages on GSCs. [53][54][55][56] While there have been reports of high M2 TAM accumulation in MES tumors, the mechanism behind this correlation remains unclear, although it has been proposed that MES tumors attract M2 TAMs. 8,57 Our work expands on prior studies investigating the relationship between TAM abundance and GBM subtype by proposing the possibility that M2 TAM secreted factors directly induce MES transition in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the study were collected from the TCGA database 15 ( https://www.cancer.gov/ccg/ ). We downloaded the data of glioma patients (n = 706) from TCGA ( http://portal.gdc.cancer.gov ) to analyze the RNA sequencing and patient information, and we used a transfer tool that was provided by GDC to capture the statistics 16 .…”
Section: Methodsmentioning
confidence: 99%